Hand replantation surgery in regional anesthesia - report of two cases - Milosavljević Ana (Srpski Arhiv za Celokupno Lekarstvo)
Introduction. Hand replantation is a microsurgical operation on completely or incompletely amputated hand during which the soft tissue and bone structures are reanastomosed and reconstructed. Blockade of peripheral nerves provides anesthesia and analgesia, but also a sympatholytic effect, improving blood flow and offering better perfusion of the replanted tissue. The aim of this paper is to show the importance of regional anesthesia for hand replantation surgery. Case report. Two male patients sustained a traumatic amputation of the hands by working on industrial machines. The patients underwent a microsurgical hand replantation. An ultrasound-guided brachial plexus block was performed through an axillary approach. A 22G, 10 cm needle was used. Bupivacaine 0.25% 30 ml and lidocaine 1.3% 30 ml without adrenaline were injected perineurally. The medial side of the upper arm was infiltrated with lidocaine since it is the area of intercostobrachial nerve innervation that remains unaffected by the brachial plexus block, preventing the pain caused by the pressure from the tourniquet. During the operation, the patients were sedated with midazolam. Postoperatively, the patients were under observation at the Intensive Care Unit. Analgesia was maintained with intravenous nonsteroidal anti-inflammatory drugs and tramadol, and a single-shot blockade of brachial plexus, intramuscular groove approach. Laboratory tests were conducted, and every three hours, the skin color and turgor, capillary refill, and tactile temperature were monitored. Conclusion. Reducing peripheral vascular resistance, preventing vasospasm, and increasing blood flow through the anastomoses increase the chance of successful replantation and reduce postoperative pain and anxiety, which overall affect patients function and comfort.